2013
DOI: 10.1155/2013/251846
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bone Marrow Mesenchymal Stem Cells in the Treatment of Acute Liver Failure

Abstract: Objective. This study is to investigate the effects of bone marrow mesenchymal stem cell (BMSC) transplantation on acute liver failure (ALF). Methods. BMSCs were separated from rat bone marrow, cultured, and identified by flow cytometry. Rat model with ALF was established by injecting D-galactosamine and lipopolysaccharide. Rats were randomly divided into the control group and BMSC transplantation group. The serum levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measured at 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…In mice, there is a lower expression of Y-RNA-1 in the liver, compared to other organs. MSC have been reported to have anti-apoptotic effects on hepatocytes [4][5][6][7] in vivo. During experimental renal injury induced by cisplatin, MSCderived microvesicles were shown to modulate the expression of several different anti-apoptotic genes or effectors of apoptosis within human tubular epithelial cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, there is a lower expression of Y-RNA-1 in the liver, compared to other organs. MSC have been reported to have anti-apoptotic effects on hepatocytes [4][5][6][7] in vivo. During experimental renal injury induced by cisplatin, MSCderived microvesicles were shown to modulate the expression of several different anti-apoptotic genes or effectors of apoptosis within human tubular epithelial cells [9].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have demonstrated that BMSCs reinforce liver regeneration and have significant suppressive effects on hepatocyte apoptosis (36)(37)(38). BMSCs suppress proapoptotic protein expression and enhance anti-apoptotic protein expression, consequently attenuating hepatocyte degeneration and subsequent apoptosis, as well as accelerating hepatocyte regeneration (39).…”
Section: Discussionmentioning
confidence: 99%
“…With a high mortality rate, early recognition and transfer to a medical care center with transplant facilities is critical and essential for ALF patients . Multiple treatments for ALF, including drug therapy, artificial liver therapy, stem cell transplantation, and liver transplantation are in current medical use for patients suffering with ALF . Additionally, there is a survival rate of approximately 75% of patients who undergo emergency liver transplantation .…”
Section: Introductionmentioning
confidence: 99%